Public Perception and Participation in Plastic Waste Management - Dwi Astuti; Aulia Rahmi Cheni; Rana Ramadhani Alfiyah Nashiza; Ilmiah (Knowledge and Environmental Science for Living and Global Health, 2025)
Plastic waste management remains a major challenge in maintaining environmental cleanliness and reducing ecosystem impacts. Community perception and active participation are essential for successful waste management at the local level. Objective: This study aims to assess public perception and participation in plastic waste management in RT 04 RW III Anduring, Padang. Methods: A descriptive survey was conducted with 50 respondents through questionnaires and direct interviews. Results: The majority of respondents (72%) had a positive perception of plastic waste management, but only 42% were actively involved beyond household-level collection and sorting. This indicates a gap between awareness and actual behavior. Implications: Strengthening environmental education and providing adequate facilities are needed to enhance participation. Conclusion: Positive perception is an important foundation, but without structural support and sustained motivation, community participation in sustainable waste management will remain limited.